Numerical simulations of rotating bubble plumes in stratified environments. Issue 8 (28th August 2017) - Fabregat Tomàs, Alexandre; Poje, Andrew C.; Özgökmen, Tamay M.; Dewar, William K.
Abstract: The effects of system rotation on the turbulent dynamics of bubble plumes evolving in stratified environments are numerically investigated by considering variations in both the system rotation rate and the gas‐phase slip velocity. The turbulent dispersion of a passive scalar injected at the source of a buoyant plume is strongly altered by the rotation of the system and the nature of the buoyancy at the source. When the plume is driven by the density defect associated with the presence of slipping gas bubbles, the location of the main lateral intrusion decreases with respect to the single‐phase case with identical inlet volume, momentum, and buoyancy fluxes. Enhanced downdrafts of carrier phase fluid result in increased turbulent mixing and short‐circuiting of detraining plume water that elevate near‐field effluent concentrations. Similarly, rotation fundamentally alters dynamic balances within the plume leading to the encroachment of the trapping height on the source and an increase in turbulent dispersion in the near field. System rotation, even at modest Rossby numbers, produces a sustained, robust, anticyclonic precession of the plume core. The effects of rotation and the presence of bubbles are cumulative. The vertical encroachment of the primary intrusion and the overall dispersion of effluent are greatest at smallest Rossby numbers and largest slip velocities. The main characteristic feature in rotating single‐phase plumes, namely the robust anticyclonic precession, persists in bubble plumes. Analysis of the momentum budgets reveal that the mechanism responsible for the organized precession, i.e., the establishment of an unstable vertical hydrostatic equilibrium related to radial cyclostrophic balance, does not differ from the single‐phase case. Key Points: Rotating gas‐bubble plumes develop organized anticyclonic precession about vertical Cyclostrophic momentum balance persists in rotating gas‐bubble plumes Rotation and interphase slipping dramatically increase near‐field plume effluent concentrations